A follow-up study of the occupations of the graduates of Bicol Regional School of Arts and Trades, 1951-1956 - Ballesfin, Victorino O. 1916- (1957)
The purpose of the author was to find possible ways and means of improving the curriculum of the school by adjusting its present course offerings to the actual needs of the students as well as the various occupations existing in the communities.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Occupations; Vocational education